2017
DOI: 10.1007/s40857-017-0101-z
|View full text |Cite
|
Sign up to set email alerts
|

Review of Underwater and In-Air Sounds Emitted by Australian and Antarctic Marine Mammals

Abstract: The study of marine soundscapes is a growing field of research. Recording hardware is becoming more accessible; there are a number of off-the-shelf autonomous recorders that can be deployed for months at a time; software analysis tools exist as shareware; raw or preprocessed recordings are freely and publicly available. However, what is missing are catalogues of commonly recorded sounds. Sounds related to geophysical events (e.g. earthquakes) and weather (e.g. wind and precipitation), to human activities (e.g.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 427 publications
(657 reference statements)
1
54
0
Order By: Relevance
“…Review of the IMOS recordings indicated presence of these vocalizations during 7 of 11 months at Pilbara and 10 of 11 months at Kimberley region between November 2012 and September 2013. Independently, 17 https://acoustic.aodn.org.au/acoustic/ Erbe et al (2017) also attributed these same signals to Omura's whales based upon comparison to spectrograms and acoustic characteristics reported in Cerchio et al (2015), stating that they are frequently recorded on Australia's Northwest Shelf and were accompanied by photographic evidence of Omura's whales, but report no detail on location(s). McCauley (2009) was the first to report on these vocalizations, attributing them to Bryde's whales before the description of Omura's whale song by Cerchio et al (2015) and the attribution of Erbe et al (2017); song was documented across an extensive range from at least ten recording sites in the waters between Exmouth (21.58 • S 113.90 • E) to north of Darwin (approximately 9.5 • S 129 • E).…”
Section: Indonesiamentioning
confidence: 99%
See 1 more Smart Citation
“…Review of the IMOS recordings indicated presence of these vocalizations during 7 of 11 months at Pilbara and 10 of 11 months at Kimberley region between November 2012 and September 2013. Independently, 17 https://acoustic.aodn.org.au/acoustic/ Erbe et al (2017) also attributed these same signals to Omura's whales based upon comparison to spectrograms and acoustic characteristics reported in Cerchio et al (2015), stating that they are frequently recorded on Australia's Northwest Shelf and were accompanied by photographic evidence of Omura's whales, but report no detail on location(s). McCauley (2009) was the first to report on these vocalizations, attributing them to Bryde's whales before the description of Omura's whale song by Cerchio et al (2015) and the attribution of Erbe et al (2017); song was documented across an extensive range from at least ten recording sites in the waters between Exmouth (21.58 • S 113.90 • E) to north of Darwin (approximately 9.5 • S 129 • E).…”
Section: Indonesiamentioning
confidence: 99%
“…Independently, 17 https://acoustic.aodn.org.au/acoustic/ Erbe et al (2017) also attributed these same signals to Omura's whales based upon comparison to spectrograms and acoustic characteristics reported in Cerchio et al (2015), stating that they are frequently recorded on Australia's Northwest Shelf and were accompanied by photographic evidence of Omura's whales, but report no detail on location(s). McCauley (2009) was the first to report on these vocalizations, attributing them to Bryde's whales before the description of Omura's whale song by Cerchio et al (2015) and the attribution of Erbe et al (2017); song was documented across an extensive range from at least ten recording sites in the waters between Exmouth (21.58 • S 113.90 • E) to north of Darwin (approximately 9.5 • S 129 • E). McCauley (2009McCauley ( , 2014 reports year-round presence of these song phrases from at least The first known account in Australia is also the most southern record for the species, a stranding of a 10.2 m individual of unknown sex in January 2000 at Black Point, Yorke Peninsula, Gulf St Vincent, South Australia, near Adelaide (Yamada et al, 2006b;Kemper, personal communication to TKY).…”
Section: Indonesiamentioning
confidence: 99%
“…Many studies use onomatopoeic names to describe sounds. This method can be problematic for comparison because sounds may be assumed similar or different depending on the perception of the analyst (Dunlop et al, 2007;Erbe et al, 2017). Here, a comparison of spectrograms showed similarities among multiple sounds in different studies, some of which were given a different onomatopoeic name ( Table 5).…”
Section: Discussionmentioning
confidence: 92%
“…According to spectrographic features, baleen whale sounds can be classified as constant-wave (CW), frequency-modulated (FM), or amplitude-modulated (AM) (Erbe et al, 2017). However, in the literature, these are frequently named and grouped according to how they are perceived by human listeners (and are given onomatopoeic names, such as grunt, growl, moan, wop, etc.).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation